Leading Beautifully: How Mastery, Congruence and Purpose Create the Aesthetic of Embodied Leadership Practice - Ladkin, Donna (Elsevier Science B.V., Amsterdam., 2008)
This paper explores the territory of leading as an embodied activity through the lens of the aesthetic category of ‘the beautiful’. Its starting point is that although much of the literature about effective leadership practice focuses on leadership behaviours, little is written about the way in which those behaviours are actually enacted. The musician, Bobby McFerrin serves as a case study for identifying three key aspects of leading beautifully: mastery, congruence between form and content, and purpose. These are further considered through reference to the concept of beauty as theorised by the philosophers Plato and Plotinus. The paper then considers how ‘leading beautifully’ might differ from other conceptualisations of leadership and discusses the particular insight it brings to understanding the nature of leading as a relational phe
Keywords: Aesthetics; Beauty; Embodiment; Leading as an artful practice; Performance